Analysis of Vitamin C in Kecombrang (Etlingera elatior) - Lis K. Djaledje; Mery Napitupulu; Siti Nuryanti (Universitas Tadulako, 2019)
Flower kecombrang contains nutrient that are beneficial to the community's nutritional improvement one of vitamin C is needed by the body and as a source of antioxidants. This study aims to determine the levels of vitamin C in flower buds and blooms. Analysis of vitamin C levels in the sample was performed by titration of the iodimetric method. The results of analysis, obtained levels of vitamin C in buds kecombrang flowers were 26.40 mg/100 g and the bloom was 44.26 mg/100 g. The data above showed that vitamin C levels in flower kecombrang increased based on the level of maturity.